Russian Federation : Fiscal Transparency Evaluation Update. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance paper on the Russian Federation provides a summary of the changes to Russia's fiscal transparency practices since 2014 and makes recommendations for further improvements. Russia has made important progress in enhancing the coverage and detail of fiscal reporting since 2014, but assurances of the quality and integrity of fiscal reporting remain incomplete. Reforms to the statistical treatment of taxes and nonfinancial assets have improved the comparability of budgets, statistics, and accounts but transparent reconciliations between the three are still not provided. It is imperative to make Rosstat fully independent of government and produce and publish metadata explaining in an accessible way how the main fiscal indicators or datasets are compiled. The ministry of finance has initiated an annual assessment of the quality of loans and will begin writing-down the value of doubtful debts from 2020. Separate detailed reconciliations of changes to revenue and expenditure are included in the documentation accompanying the annual budget.